Sunday Service at Unitarian Universalist Church of Fresno - Watkins, Howard::::::::: (1988)
Teacher is ?; Margaret Olmos in green; Robin Watkins in paisley dress, Leah Hanzlicek in blue dress/white sleeves, Patrick Hatcher in blue tee shirt